Management of Learning for Children with Special Needs an Early Age - Lilis Suwandari; Sutaryat Trisnamansyah; Hanafiah Hanafiah; Achmad Mudrikah (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This article aims to describe the concept and implementation of the management of learning for children of early age with special needs. This study systematically describes the facts found in the field and compare the conditions at both institutions verbal or sentence. Object in this research is the process of managing learning for children with special needs, early age to be a child. The process includes planning, learning, organizing, learning implementation, and supervision. methods of data collection using observation, interview and documentation. Managing learning in early childhood Bloom which combines between the child regular with children with special needs require a different management in early childhood education generally. Learning to accommodate children with different characteristics and barriers to the development of different. The results showed the presence of management learning for early childhood needs, namely in the planning of learning begins with the initial assessment to identify the peculiarities of the child to be tailored to the needs of the Program, Individual Learning in children as well as develop a curriculum that is used as a learning reference. Organizing by placing the supervising teacher or special teacher who has competence in the handling of the CREW in accordance with the division of the group of children's learning. The implementation of learning using learning model that is specified each institution, the implementation of learning activities include the opener, the core and the cover, Evaluation and assessment reports carried out to determine the development achieved in the learning process. Differences and similarities of both institutions are located on the concept and implementation in each of the management functions of learning for children with special needs. Recommendation addressed to the head of school, teachers and parents with the aim that the learning can be done well.